The Legal Measure to Regulate and Control Political Fake News on Cyberspace - Jommoon, Rattanaporn (CMU Journal of Law and Social Sciences, 2020)
This paper discusses problems of widespread of fake news or information (collectively referred to as “fake news) to visualize their different forms and consequences. The author take into account use of political fake news to influence elections in the United States by a group established in Russia and by Democrat supporters in senate election in State of Alabama, as well as the emergence of political fake news in Thailand. Although there is no indication as to whether effects of fake news are indeed drastic to the point where it successfully influences an election result, it is somewhat evident that they influence public perception and opinion. Awareness of widespread effects of fake news on social media platforms presumably began during 2016 presidential election of the United States. It is found that fake news has been widely used on social media platforms such as Facebook, Twitter, as well as Instagram, in an attempt to influence political election. Networks of fake news are established with propagandas, which are promoted later by fake account users or bots created on platforms. Fake news comes in many forms. Problems of fake news are deemed to threaten democracy and human rights, as they affect rights to be informed of news and freedom of expression. Both of public and private sectors are responsible for guarantee of these rights and freedom in form of technical and legal measures. The government should choose appropriate system to regulate and control fake news, or mechanism to investigate news source and screen news materials for the public.